Change in Soil Organic Carbon after Five Years of Continuous Winter Wheat or Switchgrass. Issue 2 (15th March 2018) - Chatterjee, Amitava; Long, Daniel S.; Pierce, Francis J.
Abstract : Core Ideas: Soil carbon sequestration under switchgrass depends on precipitation in semiarid regions. Changes in soil C were limited to the surface soil (15 cm) under switchgrass. Switchgrass and continuous winter wheat had similar biomass and soil carbon. Perennial grasses have been promoted to supply cellulose for ethanol production but possible consequences on soil organic carbon (SOC) should be assessed before adoption in a given region. Specific objectives were to (i) compare aboveground biomass C production and depth distribution of SOC content of continuous winter wheat ( Triticum aestivum L.) and switchgrass ( Panicum virgatum L.), (ii) determine the contribution of switchgrass to SOC, and (iii) characterize soil C inventories under each crop across a wide range of precipitation regimes. A 6‐yr (2008–2013) field study with winter wheat and switchgrass 'Blackwell' was conducted in northeastern Oregon. Solid set sprinkler irrigation was used to create a productivity gradient of low, medium, and high precipitation levels. The contribution of switchgrass to SOC was identified with δ 13 C measurements. Winter wheat had significantly higher 5‐yr‐average aboveground biomass C production than switchgrass across precipitation levels and winter wheat under high precipitation produced significantly higher aboveground biomass C than medium and low precipitation. After 5‐yr of cropping, SOC accrual in the 0‐ to 15‐cm depth was significantly higher under winter wheat than switchgrass in each precipitation regime. Results of δ 13 C indicated switchgrass contributed 7.9, 8.5, and 12.9% to profile SOC at low, medium, and high precipitation levels. Soil organic carbon in dry cropland is resistant to a shift in crop species. Switchgrass does not increase SOC more than continuous winter wheat in dry cropland of the semiarid Pacific Northwest.